Design of an Information System for Participants of the National Values Enhancement Program at Lemhannas RI using the Design Thinking Method - Yadi Yono; Risqy Siwi Pradini; Wahyu Teja Kusuma (Universitas Islam Indragiri, 2026)
The National Values Enhancement Program (Program Pemantapan Nilai-Nilai Kebangsaan—PPNK) of the National Resilience Institute of the Republic of Indonesia (Lemhannas RI) is a strategic program aimed at strengthening national insight, character, and national values among members of society. However, the participant registration process for PPNK is still conducted manually, resulting in several challenges, including slow information processing, a high risk of data-entry errors, and suboptimal dissemination of information to prospective participants. This study aims to develop a design prototype for the PPNK Participant Information System at Lemhannas RI by applying the Design Thinking methodology to facilitate and streamline the participant registration process. This approach was selected because it emphasizes identifying and exploring user needs, defining problems, and developing innovative, user-centered solutions. The study resulted in a PPNK Participant Information System prototype designed based on identified user requirements and incorporating training management and participant data management features. To evaluate the system's usability, the prototype was assessed using the System Usability Scale (SUS). The evaluation involved 10 respondents and yielded an average SUS score of 81.25. This score falls within the Excellent category, indicating that the proposed system is easy to use, meets user needs, and provides a positive user experience. The proposed prototype is expected to support more effective, efficient, and structured registration and participant management processes for the PPNK program at Lemhannas RI, while also serving as a foundation for developing an information system ready for implementation within the Lemhannas RI environment.